The effects of total sleep deprivation on the circadian rhythms and psychophysiological factors in military cadets; a comparison between wakefulness in light and darkness - Skálová, Kateřina; Maleček, Jan; Kolář, David; Červená, Kateřina; Kopřivová, Jana; Tufano, James; Omcirk, Dan; Padecký, Jan; Vetrovsky, Tomas; Bendová, Zdeňka (Frontiers in Physiology, 2026)
ObjectivesBoth sleep deprivation (SD) and light at night have negative effects on human health and performance. The aim of our work was to compare the intermediate effects of total SD under two lighting conditions: full indoor lighting and darkness mimicking natural nocturnal wakefulness.MethodsWe examined melatonin levels during SD nights, locomotor activity and peripheral temperature rhythms, cognitive performance, mood, hunger, glycaemia and food preference after SD and recovery sleep. Statistical evaluation included ANOVA with FDR correction and confidence intervals.ResultsSD transiently altered peripheral temperature rhythm and post-SD activity, with faster resynchronisation after SD in darkness. Subjective sleepiness increased after SD, with light at night alleviating morning sleepiness. Positive affect decreased after SD but normalised after recovery sleep in both groups. Negative affect worsened in the morning after SD in darkness. Cognitive performance declined after SD, but this effect was higher after SD in darkness. Preprandial glycaemia was higher after recovery sleep following SD in darkness, and sweet taste preference was significantly higher after SD in darkness.ConclusionLight exposure during SD may lead to lower subjective sleepiness and better cognitive performance the next morning compared to SD in darkness. However, light during SD also causes more pronounced and persistent disruptions to circadian rhythms of temperature and activity. This underscores the trade-off between the short-term benefits of nocturnal light exposure and its potential long-term impacts on circadian health.